2021
DOI: 10.1136/bjsports-2021-103999
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effect size of aerobic exercise training on the standard lipid profile in sedentary adults with three or more metabolic syndrome factors: a systematic review and meta-analysis of randomised controlled trials

Abstract: ObjectivesTo estimate the change in the standard lipid profile (SLP) of adults diagnosed with ≥3 metabolic syndrome (MetS) factors following aerobic exercise training (AET); and to investigate whether study/intervention covariates are associated with this change.DesignSystematic review with univariate meta-analysis and meta-regression.Data sourcesEnglish language searches of online databases from inception until July 2020.Eligibility criteria(1) Published randomised controlled human trials with study populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 124 publications
2
12
0
Order By: Relevance
“…The reasons may be as follows: (a) long-term unhealthy working conditions and lifestyles among young working-age adults can easily induce hyperlipidemia. Studies have shown that frequently staying up late, 46 a sedentary lifestyle, 47 , 48 long-term mental stress, 49 and work pressure 50 , 51 are common causes of abnormal lipid metabolism in younger individuals. (b) Dietary habits in younger adults may not always be well-balanced, with an excessive intake of saturated fatty acids and an insufficient intake of vitamins compared with the dietary habits of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons may be as follows: (a) long-term unhealthy working conditions and lifestyles among young working-age adults can easily induce hyperlipidemia. Studies have shown that frequently staying up late, 46 a sedentary lifestyle, 47 , 48 long-term mental stress, 49 and work pressure 50 , 51 are common causes of abnormal lipid metabolism in younger individuals. (b) Dietary habits in younger adults may not always be well-balanced, with an excessive intake of saturated fatty acids and an insufficient intake of vitamins compared with the dietary habits of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The blood lipid outcome measures showed positive changes in TG, Chol, and HDL at follow-up, but, somewhat paradoxically, negative changes (increased values) in LDL. Previous research has shown that HDL is the lipid fraction most sensitive to increased PA, while PA of increased intensity is typically required to reduce LDL and TG levels [ 7 , 51 , 52 ]. However, the findings of PA-induced effects on LDL are inconsistent, and are considered to be linked to variations in human weight [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firmly established evidence supports the positive effects of physical activity (PA) on health and longevity [ 1 , 2 ] and regular PA is considered essential for the prevention and treatment of several diseases [ 3 ]. Metabolic syndrome (MetS), which includes being overweight, and exhibiting abdominal obesity, insulin resistance, dyslipidaemia, and hypertension in various combinations, increases the risks of cardiovascular disease (CVD), type 2 diabetes (DM), and premature death [ 4 , 5 ], and is positively influenced by regular PA [ 6 , 7 ]. The recently updated recommendations for physical activity among adults include a target of 150–300 min per week of moderate-intensity aerobic PA, or 75–150 min per week of vigorous-intensity aerobic PA [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this analysis showed that the aerobic exercise training improved all lipid profile. Interestingly, the intensity of exercise was correlated with the reduction of TG, while the volume was associated with increase of HDL-cholesterol [ 57 ]. Non-alcoholic fatty liver disease (NAFLD) can be considered the hepatic manifestation of lipids disorder [ 58 ], and at the same time is an independent determinant of CV risk, To note that tit has been documented that the regular physical activity is also capable to improve the liver damage [ 59 ].…”
Section: Exercise and Primary CV Preventionmentioning
confidence: 99%